The non-human animal body as an audiovisual metaphor of cultural conflicts and identities - Martinelli, Dario; Lankauskaitė, Viktorija (Comunicación y Medios, 2022)
In audiovisual arts, the inclusion of non-human animal (NHAs) bodies, is not rare, and it often helps to make a point about humanity and human nature. In such works, NHAs and their corporeality embody not just themselves, but rather act as human symbols, projections, stereotypes, allegories, taboos, myths, and superstitions. A close reading of Wes Anderson’s feature film Isle of Dogs (2018) provides an analysis of how the representation of dogs constitutes allegories of discrimination and bias against the Other. Among other parameters, physiology and aesthetic appearance are the most prominent ones when it comes to basis of discrimination and its representation. The associated features of shape, and senses and channels inform about human view towards the natural world and the tendency to put everything to certain use. Finally, the level of hybridisation from the filmmaking perspective, helps to illustrate the irrationality of such discrimination.